John Buridan: The Human Body at the Intersection of Natural Philosophy and Medicine - Beneduce, Chiara (American catholic philosophical quarterly, 2023)
This article considers the relationship between John Buridan's natural philosophy and medicine. By examining some aspects of Buridan's description of the human body related to sensation, nutrition, and generation - especially as they were framed in the so-called "controversy between philosophers and physicians" - this article shows that, though mostly faithful to Aristotelian doctrine, Buridan's theoretical biology relies to a large extent on medical ideas.